Valorization of Algerian Semi-Soft Date and Traditional Preparation of Date Syrup: Physicochemical and Biochemical Properties - Laouar, Asma; Benbelkhir, Amina; Baida, Wahiba; Rouissat, Linda; BENYAGOUB, Elhassan (Department of Technology of Agricultural product (THP) Jambi University, 2021)
In Algeria, the production of dates occupies a large part of Saharan agricultural production. The wilaya of Bechar is one of the most productive regions for dates, where more than half of their production is considered as a second quality dates which are sold by barter or used as animal feed. Families in these regions use this type of date to prepare by-products, namely; date syrup locally called